2022
DOI: 10.3389/fped.2022.874425
|View full text |Cite
|
Sign up to set email alerts
|

The SES-CD Could Be a Predictor of Short- and Long-Term Mucosal Healing After Exclusive Enteral Nutrition in Pediatric Crohn’s Disease Patients

Abstract: AimsTo explore the predictors of mucosal healing (MH) for short- and long-term after exclusive enteral nutrition (EEN) in pediatric Crohn’s disease (CD) patients.MethodsA retrospective analysis was performed for newly diagnosed active CD patients admitted to our center from January 2017 to 30 December 2020, who were treated with EEN for induction therapy with a minimum of 12 months of follow-up post-EEN. According to the simple endoscopic score for CD (SES-CD), at 1-year post-EEN, 17 patients with an SES-CD &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Similar results were observed in patients who received anti-TNF-α therapy. 22 These findings indicate that early MH is important for patients with CD, 4,5,29 especially those with moderate to severe lesions at baseline. Both EEN and anti-TNF-α therapy reportedly induce early MH, 9,30,31 but few studies have systematically compared their differences with regard to early MH.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Similar results were observed in patients who received anti-TNF-α therapy. 22 These findings indicate that early MH is important for patients with CD, 4,5,29 especially those with moderate to severe lesions at baseline. Both EEN and anti-TNF-α therapy reportedly induce early MH, 9,30,31 but few studies have systematically compared their differences with regard to early MH.…”
Section: Discussionmentioning
confidence: 87%
“…Notably, lesions in the terminal ileum and right colon were worse than those in other ileocolonic segments at baseline, and these results were consistent with our previous study. 5 A study indicated that ileal involvement might predict better clinical outcomes for EEN therapy, 12 and isolated colonic CD was associated with a poorer response to EEN. 13 These results are not consistent with ours, possibly because of the different primary outcomes, as clinical remission was the main outcome in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictors of response to treatment are important to inform clinical decisions on patient management. Milder endoscopic disease, at baseline, was the sole predictor of mucosal healing both at EEN completion and after one year of follow-up in a recent retrospective study in 50 children in China [13]. Likewise, in a retrospective study among 366 children with CD in Italy, age >15 years and a Paediatric Crohn's Disease Activity Index >50 were associated with lower response rates [14].…”
Section: Key Pointsmentioning
confidence: 92%
“…The authors recommended that children with CD with a simple endoscopic score for CD cut-off value > 11.5 should be treated with biologics. 37 T A B L E 2 Evidence tables of studies which explored aspects of treatment precision/stratification in patients with Crohn's disease on exclusive enteral nutrition.…”
Section: Clinical and Laboratory Parametersmentioning
confidence: 99%